miR-4270 suppresses hepatocellular carcinoma progression by inhibiting DNMT3A-mediated methylation of HGFAC promoter - Zou, Qiang; Cao, Shasha (PeerJ, 2023)
Background miR-4270 is a regulatory factor has been linked with the progression of various cancers, such as nasopharyngeal carcinoma, hepatocellular carcinoma (HCC), and gastric cancer. However, the underlying mechanisms through which miR-4270 modulates HCC development are not fully understood. Methods miR-4270 expression levels were analyzed in various HCC cell lines and tissue samples. An online bioinformatics tool was then utilized to predict the miR-4270 target gene. The binding relationship between miR-4270 and its target gene DNMT3A was verified using dual-luciferase reporter and Ago2–RIP assays. Then, co-immunoprecipitation (Co-IP) and chromatin immunoprecipitation (ChIP) assays were conducted to investigate the association between DNMT3A and the hepatocyte growth factor activator (HGFAC) promoter region. To assess the methylation level of the HGFAC promoter, methylation-specific PCR (MSP) was employed. Furthermore, rescue analyses were carried out to evaluate the functional relevance of miR-4270 and HGFAC in the modulation of the malignant properties of HCC cells. Finally, HepG2 cells overexpressing miR-4270 were subcutaneously injected into nude mice to estimate the impact of miR-4270 on the xenograft tumor growth of HCC. Results A substantial miR-4270 downregulation was revealed in HCC patient samples and cell lines. miR-4270 upregulation suppressed both cell proliferation and invasion while promoting apoptosis. At the molecular level, miR-4270 was found to bind to the 3′untranslated region (3′UTR) of DNMT3A, thereby inhibiting DNMT3A-mediated methylation of the HGFAC promoter. Functional assays indicated that inhibition of miR-4270 stimulated HCC cell growth, an effect counteracted by overexpression of HGFAC. In vivo assays further verified that miR-4270 effectively suppressed the progression of HCC xenograft tumors. Conclusions miR-4270 was found to mitigate the malignant characteristics of HCC by inhibiting DNMT3A-mediated methylation of the HGFAC promoter, suggesting a potential therapeutic avenue for the management of HCC.
Keywords: Hepatocellular carcinoma; miR-4270; DNMT3A; HGFAC